2007
DOI: 10.1542/peds.2006-3087
|View full text |Cite
|
Sign up to set email alerts
|

Therapy for Head Lice Based on Life Cycle, Resistance, and Safety Considerations

Abstract: The timing of head lice maturation most favorable to their survival in the presence of anti-lice agents is the maximum time as an ovum (12 days) and the shortest possible time of maturing from newly hatched nymph to egg-laying adult (8.5 days). Pediculicides that are not reliably ovicidal (pyrethroids and lindane) require 2 to 3 treatment cycles to eradicate lice. Ovicidal therapies (malathion) require 1 to 2 treatments. Treatment with an agent to which there is genetic resistance is unproductive. In the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 63 publications
2
63
1
3
Order By: Relevance
“…The features described by Mougabure Cueto et al were also observed in our experiment, but age of head lice eggs in that study was not known, because the eggs had been collected from infested individuals. Lebwohl (2007) [29] described the life cycle of head lice and states that hatching occurred after 7-12 days, while our findings showed a delay of two days, with hatching starting on day 9. The delay in our experiments might be due to the lower temperature of incubation, as compared to the human scalp, known to delay development and hatching [14].…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The features described by Mougabure Cueto et al were also observed in our experiment, but age of head lice eggs in that study was not known, because the eggs had been collected from infested individuals. Lebwohl (2007) [29] described the life cycle of head lice and states that hatching occurred after 7-12 days, while our findings showed a delay of two days, with hatching starting on day 9. The delay in our experiments might be due to the lower temperature of incubation, as compared to the human scalp, known to delay development and hatching [14].…”
Section: Discussioncontrasting
confidence: 48%
“…High concentrations of antibiotics added to the blood in the automated feeding apparatus might have negatively affected the fecundity of head lice eggs [11]. Antibiotics have been discussed as a treatment option for pediculosis, as they may eliminate symbiotic bacteria found in the lices' guts [2,[28][29][30]. Unfortunately, only first instar nymphs can be trained to feed through the membrane, so that an a priori selection of lice occurs, resulting in a strain of lice distinct from wild strains, especially when maintained in the apparatus for various generations.…”
Section: Discussionmentioning
confidence: 99%
“…8,30 An alternate treatment schedule on days 0, 7, and 13 to 15 has been proposed for nonovicidal products. 31 Resistance to 1% permethrin has been reported, 8,[32][33][34][35] but the prevalence of this resistance is not known. .…”
Section: Permethrin (1%)mentioning
confidence: 99%
“…An alternate schedule of 3 treatments with nonovicidal products on days 0, 7, and 13 to 15 has been proposed. 31 Although pyrethrins were extremely effective when introduced in the mid-1980s, recent study results have indicated that efficacy has decreased substantially because of development of resistance. 6 The prevalence of resistance has not been systematically studied but seems to be highly variable from community to community and country to country.…”
Section: Permethrin (1%)mentioning
confidence: 99%
“…Using rimethoprimsulfam-ethoxazole for head louse treatment is still controversial [10,12]. Head louse is more prevalent among countries having poor living condition, this study was carried out in District Mardan because head louse is also big problem for students of district Mardan, this study was carried out to reveal the diverse factors responsible for head louse prevalence among students and aware people to control its prevalence.…”
Section: Introductionmentioning
confidence: 99%